Combining and Balancing Project-Based and Blended Learning in Education - Knoblauch, Christoph (International Journal of Advanced Corporate Learning (iJAC), 2022)
This paper discusses evaluation findings from project-based and blended learning courses in the higher education sector and beyond. The multi-method studies focus on learners’ attitudes, practices and preferences towards project-based and blended learning. The evaluated courses were developed and taught in the context of teacher training programs at Ludwigsburg University of Education (LUE). They aim at the planning, execution and critical reflection of individual projects carried out by the participating students in blended learning contexts. This paper presents a discussion of the structure, the blended methodology and the outcomes of the courses, combining the methods of quantitative evaluation research and qualitative interviews. By doing so, the study assesses current practice and analyses the above-mentioned courses closely and in detail. Thus, this paper discusses how students deal with a project-based and blended learning environment and how these results can be constructively implemented to improve future project-based and blended learning scenarios.